SISTEM INFORMASI MANAJEMEN PEMASARAN KOPI ARABIKA SUBAK ABIAN ULIAN MURNI, KINTAMANI, BANGLI BERBASIS WEB - Yudiastina, I Gst. Bgs. Arya; Satriawan, I Ketut; Agus Sanjaya, Ngurah (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 3 No 3 (2015): September)
Subak Abian Ulian Murni is a business unit engaged in the processing of arabica coffee. Marketing of arabica coffee at Subak Abian Ulian Murni currently is still using a conventional marketing system. This causes the conducted marketing is not optimal, so a new marketing system is required. Management information system of marketing arabica coffee web based is one solution of existing problems. The purposes of this research were to produce management information system of marketing arabica coffee Subak Abian Ulian Murni web based and determine key factors in the design of the system. Design system of this research used a structured approach method and system development method using waterfall model. The tools were used in the design of the system i.e.: flowchart, context diagram, and data flow diagram (DFD), as well as software includes Wordpress, PHP, and MySQL. The research showed that management information system of marketing arabica coffee Subak Abian Ulian Murni web based has been resulted. Key factor of this system design were design, content, and usability. The results of an assessment of the website quality showed that respondents said the quality of the design is between good and very good, the content served was nearing complete, and usability was easy to used.
Keywords: 62,